Automatic air temperature control in a container with an optic-variable wall. (15th August 2018) - Wang, C.; Zhu, Y.; Qu, J.; Hu, H.D.
Highlights: Automatic air temperature control is proposed for energy saving in containers. With OVW, air is simultaneously kept cool in summer and warm in winter. Adjustment of solar radiation with OVW is verified experimentally in winter. Abstract: Solar energy is one important source of sustainable and green energy. However, solar radiation is not always demanded as heat source for building in seasons. Automatic air temperature control with an optic-variable wall is proposed in this paper to reduce the HVAC (Heating, Ventilation & Air-Conditioning) energy consumption in containers. The feasibility of an optic-variable wall (OVW) is first verified with sample-test on the color, reflectivity and absorbance with UV 3600. The reference for relectivity test is BaSO4 and the reference for absorbance test is quartz. The feasibility of its performance on air temperature control inside a container is verified with preliminary experiments under natural winter conditions at a low ambient temperature. It is checked that the color of OVW varies from dark at low temperature to light at high temperature. The reflectivity of OVW is small at low temperature and high at high temperature. Then, the theoretical investigation on air temperature inside a container is conducted. It is concluded that air inside a container is simultaneously kept cool in summer and warm in winter, with the adoption of OVW. The stable air temperature rise is small under the conditions of high ambient temperature and large solar radiation, leading to the potential of less energy consumption for cooling in summer, while it is large under the conditions of low ambient temperature and small solar radiation, leading to the potential of less energy consumption for heating in winter. The variation range of the stable air temperature with OVW is also narrower. The results are helpful for green design and energy saving in containers.